LITERATURE REVIEW: PENGAPLIKASIAN 16 PERSONALITY FACTOR DALAM REKRUTMEN - Ajeng Eka; Nur Eva (Universitas Negeri Malang, 2022)
Abstract: A company or organization in recruiting prospective employees must choose employees who have the same goals as the company and choose prospective employees who have good performance in the company. In a previous study entitled to conclude that employee performance is influenced by positive attitudes and personality of employees by 32.99% while 67.01% is caused by other factors not examined. This shows that there is a positive influence of attitude and personality on employee performance. For this reason, it is necessary to hold a personality test to predict employee performance in the future. One of the personality tests, namely the 16 personality factor test, is a personality test developed by Raymond Cattell. This test is composed of 16 structured personality factors. So that researchers will examine whether the application of 16 PF has valid results in employee recruitment and explain how 16 PF can predict personality. In researchers using the literature review method from this study it is stated that 16 PF can predict personality to choose prospective employees in the company appropriately Keywords: recruitment, personality, 16 PF, performance, employees. Abstrak: Suatu perusahaan atau organisasi dalam melakukan rekrutmen calon karyawan haruslah memilih karyawan yang memiliki tujuan yang sama dengan perusahan dan memilih calon karyawan yang memiliki kinerja yang baik dalam perusahaan tersebut. Pada Penelitian sebelumnya berjudul menyimpulkan bahwa kinerja pegawai dipengaruhi oleh sikap dan kepribadian positif pegawai sebesar 32,99 % Sedangkan 67,01 % disebabkan oleh faktor lain yang tidak diteliti. Hal ini menunjukkan bahwa adanya pengaruh positif dari sikap dan kepribadian terhadap kinerja karyawan.Untuk itu perlu diadakan tes kepribadian guna memprediksi kinerja karyawan di masa depan. Salah satu tes kepribadian yaitu tes 16 personality factor merupakan tes kepribadian yang dikembangkan oleh Raymond Cattell. Tes ini disusun 16 faktor kepribadian yang terstruktur. Sehingga peneliti akan mengkaji apakah pengaplikasian 16 PF memiliki hasil valid dalam rekrutmen karyawan dan menjelaskan bagaimana 16 PF dapat memprediksi kepribadian. Dalam peneliti menggunakan metode literature review dari penelitian ini dinyatakan bahwa 16 PF dapat memprediksi kepribadian untuk memilih calon karyawan yang di perusahaan dengan tepat. Kata kunci rekrutmen, kepribadiaan, 16 PF , karyawan